Comparison of the effects of social skills training and functional analytic therapy on the social skills of a patient with social phobia (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This study aimed to compare the effects of FAP and social skills training interventions on behaviors related to social skills class of a social phobic adult participant, to assess the level of anxiety during the intervention and between sessions, and to compare the results of the SPIN and IHS (Social Skills Inventory) before and after the intervention. For that, an AB1CB2 was used, where A was the baseline phase, B1 and B2 were phases on which a class of behavior was submitted to FAP interventions and another class was submitted to social skill training interventions, and C was the intervention phase on which the class of behavior was submitted to social skill training interventions and another was submitted to FAP interventions. The results showed an increase in the frequency of occurrence of classes throughout the sessions in both interventions, with highest frequencies obtained in the FAP sessions. The level of anxiety related in social skill training sessions was higher than those related in FAP. The measures obtained with the inventories were similar before and after the interventions. The results indicated that FAP may be effective in the interventions for social skill behaviors.
Keywords: social skill; social anxiety; social phobia; FAP; social skills training